PENGELOLAAN ARSIP DINAMIS PADA SUBBIDANG PENGELOLAAN DOKUMEN PEGAWAI DI BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN KABUPATEN KUTAI TIMUR - Reza Laksana Putra; Bambang Irawan; Farhanuddin Jamanie (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
This study aims to describe the management of dynamic archives in the Personnel Education and Training Agency for employee document management in East Kutai Regency. This type of research is descriptive qualitative. The technique of collecting data through interviews, observation and documentation and analyzed using an interactive analysis model. The results showed that Dynamic Archive Management in the SIAK sector, especially in the Sub-Division of Employee Document Management in East Kutai Regency, has been carried out well in the creation of archives, but in terms of use, maintenance and shrinkage have not been fully implemented, this can be seen from the use of files that are not in accordance with SOP is determined, then in maintenance there is no special room that meets standards such as the absence of room temperature regulation, air ventilation, and the lack of filing cabinets. Furthermore, for the depreciation or destruction of the archive has never been done which causes the archive is not known to be due for its destruction (archive retention).Keywords: Records Management, Dynamic Archives, Archive Maintenance, Archive Shrinking